Emerging Pharmacological Treatments to Prevent Abdominal Aortic Aneurysm Growth and Rupture - A. Fraga-Silva, Rodrigo; Trachet, Bram; Stergiopulos, Nikolaos (Current Pharmaceutical Design, 2015)
Abdominal aortic aneurysm (AAA) is a local expansion of the abdominal aorta wall caused by a complex multifactorial maladaptive vascular remodeling. Despite recent advances in the management of cardiovascular diseases, there currently is no established drug therapy for AAA. Since the probability of death from a ruptured AAA still remains high, preventive elective repair of AAAs larger than 5.5 cm in luminal diameter is considered the best treatment option. However, perioperative complications are problematic as elective AAA repair comes with numerous intrinsic risks. Impelled by the need of improving AAA therapy, significant efforts have been made to identify pharmacological tools that would slow down AAA enlargement and lower the risk of rupture, thereby reducing the necessity of surgical intervention. In this review, we discuss recent findings addressing molecular targets that could potentially treat AAA, particularly addressing: statins, classical renin angiotensin system (RAS) blockers, the protective arm of RAS, renin inhibitors, tetracyclines, interleukin-1β inhibition, anti-angiogenic agents and urocortins.
Keywords: statins